Analisis Manajemen Pembiayaan di SMP Negeri 40 Kota Bandung: Analisis Manajemen Pembiayaan di SMP Negeri 40 Kota Bandung - Sugianti, Riestha; Suryadi; Fitroh Hayati (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
This research analyzes the standard financing policy implemented at SMP Negeri 40 Bandung City in 2023. Each educational unit requires operational costs to carry out scheduled programs, new programs that will be implemented, as well as planning activities for school development in the future. front. The elementary school fee policy is determined by taking into account the technical guidelines for the use of BOS funds to ensure the efficiency and effectiveness of school financial management. Schools have the authority to manage secondary education operational costs, but in implementation they must always be guided by the provisions that have been determined. The method used is qualitative with interviews and observations. Based on research findings, the most dominant source of education financing is School Operational Assistance (BOS) funds, with an allocation of IDR 1,084,761,343. This shows that the government through the BOS program makes a very significant contribution in ensuring the continuity of the teaching and learning process in schools. Implementation of education financing begins with a planning process contained in the School Work Plan (RKS) and School Activity and Budget Plan (RKAS).